2005
DOI: 10.1080/03009740510026634
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐cyclic citrullinated peptide: diagnostic and prognostic values in juvenile idiopathic arthritis and rheumatoid arthritis in a Chinese population

Abstract: The anti-CCP antibody assay is a valuable tool for the diagnosis of RA and a subset of JIA in Chinese patients. It could be a useful predictive test for joint erosion in JIA of the polyarticular RF-positive subset and may be influential in the choice of the best therapeutic strategy in patients with recent-onset arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 30 publications
5
41
1
4
Order By: Relevance
“…Our findings showed that the prevalence rates of all ACPAs in the whole population of JIA patients were less than 30% and much lower than those of adult RA patients, which agrees with the results reported in previous studies on anti-CCP (Avcin et al, 2002;Bongi et al, 2004;Kasapçopur et al, 2004;Kwok et al, 2005;Gilliam et al, 2011;Tebo et al, 2012). Therefore, we confirmed that ACPAs cannot serve as screening biomarkers for the general JIA population due to their low sensitivity.…”
Section: Discussionsupporting
confidence: 81%
“…Our findings showed that the prevalence rates of all ACPAs in the whole population of JIA patients were less than 30% and much lower than those of adult RA patients, which agrees with the results reported in previous studies on anti-CCP (Avcin et al, 2002;Bongi et al, 2004;Kasapçopur et al, 2004;Kwok et al, 2005;Gilliam et al, 2011;Tebo et al, 2012). Therefore, we confirmed that ACPAs cannot serve as screening biomarkers for the general JIA population due to their low sensitivity.…”
Section: Discussionsupporting
confidence: 81%
“…Numerous studies have shown that IgM RF-positive polyarthritis patients have a higher prevalence of anti-CCP antibodies [36][37][38][39][40][41][42][43][44]45 We have also shown that the measurement of IgA, IgM, and IgG anti-CCP antibody isotypes early in the course of JIA may be beneficial to distinguish aggressive disease and possibly initiate more aggressive treatment earlier in those patients [48•]. These patients have been shown to have higher immune complex levels by the anti-Fc III method of detection and are noted to have increased disease activity [49•].…”
Section: Discussionmentioning
confidence: 99%
“…Kwok et al [41] evaluated anti-CCP antibodies using second generation peptides in a Chinese cohort of JIA patients and found 6 of 59 (10%) with elevated anti-CCP antibodies. Similar to previous findings [36][37][38][39][40], 80% (4/5) of their cohort with elevated anti-CCP antibodies had IgM RF-positive polyarthritis.…”
Section: Anticyclic Citrullinated Peptide Antibodiesmentioning
confidence: 98%
“…Anti-CCP is present in the serum of a portion of RA patients and has been identified in the serum of patients at all stages of RA: preclinical, early, and established (Taylor et al 2011). In clinical research studies, anti-CCP antibodies were found in 55-69% of patients with RA (Kwok et al 2005) and 65% of RA patients with late-onset RA (Lopez-Hoyos et al 2004). Recent clinical trials suggest that anti-CCP is highly accurate in selectively identifying RA patients (Nikolaisen et al 2007;Quinn et al 2006) and is of particular diagnostic use in patients who are negative for RF (Quinn et al 2006) and an indicator of prognosis (Bas 2005).…”
Section: Foot Involvement In Rheumatoid Arthritismentioning
confidence: 98%